CORRELATION BETWEEN WAIST-HIP RATIO AND WAIST CIRCUMFERENCE AS A PREDICTOR PARAMETER IN FRAMINGHAM RISK SCORE FOR HARD CORONARY HEART DISEASE AND KIDNEY FUNCTION (CARDIO-RENAL SYNDROME) - Teguh, Stanislas; Priyana, Andria; Kartika, Ronald; Firmansyah, Yohanes; Santoso, Alexander (Prosiding Seminar Nasional COSMIC Kedokteran, 2025)
Cardio-renal syndrome reflects the intricate link between heart and kidney health, where the dysfunction of one organ worsens the other. In coronary heart disease, the Framingham Risk Score (FRS) is a key tool for estimating the 10-year risk of myocardial infarction (MI) or death. Abdominal obesity, often measured by waist-hip ratio (WHR), has emerged as an important cardiovascular risk factor, potentially enhancing existing predictive models. This study aimed to evaluate the correlation between FRS for Hard Coronary Heart Disease and kidney function (Cardio-Renal Syndrome) and to assess WHR as a predictive parameter for FRS. This study conduct a cross-sectional study among 52 employees of Yayasan Kalam Kudus, it analyzed the correlation between FRS ("10-year risk of MI or death" and "Average 10-year risk of MI or death"), kidney function decline, waist circumference, and WHR using Spearman's correlation. Significant correlations were found between "10-year risk of MI or death" and kidney function decline (r: -0.381; p: 0.005), waist circumference (r: 0.274; p: 0.050), and WHR (r: 0.333; p: 0.016). Similarly, "Average 10-year risk" correlated with kidney function decline (r: -0.376; p: 0.006) and WHR (r: 0.291; p: 0.036). The study highlights a meaningful link between FRS, kidney function, and abdominal obesity. These findings support the inclusion of WHR and waist circumference in coronary risk assessments, particularly for populations at risk of cardio-renal syndrome.